Isocyanides as Influenza A Virus Subtype H5N1 Wild‐Type M2 Channel Inhibitors. Issue 11 (7th September 2015) - Wu, Shuwen; Huang, Jing; Gazzarrini, Sabrina; He, Si; Chen, Lihua; Li, Jun; Xing, Li; Li, Chufang; Chen, Ling; Neochoritis, Constantinos G.; Liao, George P.; Zhou, Haibing; et al.
Abstract: Basic bulky amines such as amantadine are well‐characterized M2 channel blockers, useful for treating influenza. Herein we report our surprising findings that charge‐neutral, bulky isocyanides exhibit activities similar to—or even higher than—that of amantadine. We also demonstrate that these isocyanides have potent growth inhibitory activity against the H5N1 virus. The −NH2 to −N≡C group replacement within current anti‐influenza drugs was found to give compounds with high activities at low‐micromolar concentrations. For example, a tenfold improvement in potency was observed for 1‐isocyanoadamantane (27 ), with an EC50 value of 0.487 μm against amantadine‐sensitive H5N1 virus as determined by both MTT and plaque‐reduction assays, without showing cytotoxicity. Furthermore, the isocyanide analogues synthesized in this study did not inhibit the V27A or S31N mutant M2 ion channels, according to electrophysiology experiments, and did not exhibit activity against amantadine‐resistant virus strains. Abstract : Charge‐neutral bulky isocyanides were found to exhibit antiviral activities similar to—or even higher than—that of amantadine. Moreover, we demonstrated that these isocyanides have potent growth inhibitory activity against the wild‐type H5N1 virus. The NH2 to N≡C group replacement within current anti‐influenza drugs was found to result in compounds with low‐micromolar activities.